Convergence analysis of Newton method without inversion for solving discrete algebraic Riccati equations. Issue 14 (September 2022) - Erfanifar, Raziyeh; Sayevand, Khosro; Hajarian, Masoud
Abstract: In this paper, we first introduce the necessary and sufficient conditions for the existence of the solution of discrete algebraic Riccati equation. Then we propose the Newton method without inversion to find the solution of the discrete algebraic Riccati equation. We show that the proposed method converges to a positive definite solution of the discrete algebraic Riccati equation. Finally, the accuracy and effectiveness of the proposed method in compare to some existing algorithms are demonstrated by various numerical examples.